Revolutionizing the global stock market harnessing blockchain for enhanced adaptability - Geada, Nuno 1983-; Sidana, Ajay 1973-; Sood, Rohit 1984- (IGI Global, 2024)
In the aftermath of the profound fiscal crisis of 2008, the very foundation of the global financial system came under intense scrutiny. The ensuing crash laid bare systemic vulnerabilities and underscored the urgent need for alternative solutions capable of fostering a more transparent and resilient model. This period of economic turbulence exposed critical flaws in the existing global financial infrastructure, prompting a search for innovations that could instill accountability, security, and transparency. It is against this backdrop of financial upheaval that Revolutionizing the Global Stock Market: Harnessing Blockchain for Enhanced Adaptability explores the solutions poised to redefine the dynamics of the stock market. Revolutionizing the Global Stock Market: Harnessing Blockchain for Enhanced Adaptability strategically addresses the objectives crucial for navigating the complexities of the contemporary business landscape. The focus extends beyond survival to thriving, emphasizing the persistence of big-picture perspectives, adaptability to new productivity approaches, and the importance of clear and consistent communication. These objectives also encompass facilitating avenues for employee feedback, fostering continuous improvement, and constructing business continuity plans with inherent elasticity. By offering both a theoretical and practical foundation, the book aims to be an indispensable resource for organizations, managers, and scholars navigating the potential of blockchain technology in the context of the global stock market.